How to Organize a Large-Scale Ecological Restoration Program? The Framework Developed by the Atlantic Forest Restoration Pact in Brazil - Brancalion, Pedro H. S; Viani, Ricardo A. G; Calmon, Miguel; Carrascosa, Helena; Rodrigues, Ricardo R (Journal of sustainable forestry, 2013)
Large-scale ecological restoration programs across the world have begun to extensively transform degraded lands into young native ecosystems. However, more projects like these will be necessary in the coming years to fulfill the goal of restoring 150 million ha established by United Nations Convention on Biological Diversity. Here, we present and discuss the steps required for and the lessons learned from the organization of a large-scale ecological restoration program in Brazil, the Atlantic Forest Restoration Pact. These lessons are organized around 9 steps: (a) the presentation of the motivations driving the promotion of large-scale restoration, (b) the organization of the main stakeholders, (c) the definition of goals, (d) the organization of a database, (e) the indication of both available and priority areas for restoration, (f) the proposal of science-based and field-validated methods, (g) the establishment of a monitoring protocol, (h) the proposal of a communication program to unite members and interact with society, and (i) the strategies for promoting the establishment of public policies conducive to restoration. This framework may provide a template to help other initiatives to mainstream isolated restoration projects into a large and well-organized movement, which may increase the chances of successful restoration in the future.